2020
DOI: 10.3390/ijms22010117
|View full text |Cite
|
Sign up to set email alerts
|

Plant Responses to Heat Stress: Physiology, Transcription, Noncoding RNAs, and Epigenetics

Abstract: Global warming has increased the frequency of extreme high temperature events. High temperature is a major abiotic stress that limits the growth and production of plants. Therefore, the plant response to heat stress (HS) has been a focus of research. However, the plant response to HS involves complex physiological traits and molecular or gene networks that are not fully understood. Here, we review recent progress in the physiological (photosynthesis, cell membrane thermostability, oxidative damage, and others)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
165
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(167 citation statements)
references
References 102 publications
2
165
0
Order By: Relevance
“…The expression of HSPs in plants is regulated by epigenetics, such as DNA methylation, histone modification, and chromatin remodeling ( Boyko et al, 2010 ; Gao et al, 2014 ; Gallego-Bartolomé, 2020 ; Zhao et al, 2021 ). HSPs gene must be unwrapped from histones to become actively transcribed when HSF1As are bound to HSEs ( Figure 1 ).…”
Section: Heat Sensing and Signaling In Land Plantsmentioning
confidence: 99%
See 3 more Smart Citations
“…The expression of HSPs in plants is regulated by epigenetics, such as DNA methylation, histone modification, and chromatin remodeling ( Boyko et al, 2010 ; Gao et al, 2014 ; Gallego-Bartolomé, 2020 ; Zhao et al, 2021 ). HSPs gene must be unwrapped from histones to become actively transcribed when HSF1As are bound to HSEs ( Figure 1 ).…”
Section: Heat Sensing and Signaling In Land Plantsmentioning
confidence: 99%
“…Histone chemical modifications, such as methylation and acetylation, have been also indicated to be important for the regulation of HSPs in plants ( Lämke et al, 2016 ; Yamaguchi et al, 2021 ). Regarding non-coding RNA (ncRNA), such as microRNAs (miRNAs) and small interfering RNAs (siRNAs), its involvement in the regulation of the HSR has been suggested in several land plant species ( Khraiwesh et al, 2012 ; Li et al, 2014 ; Zhao et al, 2016 ; Liu et al, 2017 ; Lin J. S. et al, 2018 ; Zhao et al, 2021 ). Thus, following a short period of HS, epigenetic processes have also been implicated in developing a transcriptional heat memory ( Bäurle and Trindade, 2020 ).…”
Section: Heat Sensing and Signaling In Land Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plants exposed to high temperature (heat stress, HS), significant abiotic stress due to increased global warming, suffer from severe, and sometimes lethal, adverse effects. Plants have evolved complex mechanisms to respond to this kind of stress in order to cope with such conditions [132]. Another study on rice and heat stress found that OsFIE1 facilitated seed size reduction (fertilization-independent endosperm).…”
Section: Heat-induced Stressmentioning
confidence: 99%